Legal Analysis of Online Gambling and Its Criminal Threats Reviewed from Article 45 Paragraph (2) of Law Number 19 of 2016 concerning Electronic Information and Transactions - Amri, Helmika Suradi; Risdalina, Risdalina; Munthe, Indra Kumalasari (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
Poverty that occurs in society has a bad influence on one's behavior and character. The occurrence of poverty is the impact of reduced employment opportunities that do not give someone the opportunity to do work in making money. One way a person makes money quickly and the easy way is by doing online gambling. Perpetrators of online gambling crimes include various groups, both old and young, entrepreneurs, workers, unemployed, men and women, in cities and villages Online gambling activities have caused many losses to the community. Eradicating online gambling is not an easy thing, this requires the role of responsive stakeholders in eradicating online gambling. Furthermore, each competent party in their field must continue to coordinate with ministries and institutions, digital platforms, cellular operators and internet service providers, banks and financial service providers for handling online gambling. The type of research used is the type of normative legal research. Normative law research uses normative case studies in the form of legal behavior products, for example reviewing laws. Results of discussion 1. Legal regulations regarding online gambling are reviewed from Law Number 19 of 2016 concerning Electronic Information and Transactions (ITE) Article 27 paragraph (2): everyone intentionally and without rights distributes and or transmits and or makes accessible electronic information and / or electronic documents that have gambling content, Article 45 paragraph (2) Everyone who intentionally and without rights distributes and / or transmits and / or makes accessible Electronic Information and/or Electronic Documents that have gambling content as referred to in Article 27 paragraph (2) shall be punished with a maximum imprisonment of 6 (six) years and/or a maximum fine of Rp1,000,000,000.00 (one billion rupiah), Article 45A paragraph (1)Any person who intentionally and without rights disseminates false and misleading news that results in consumer losses in Electronic Transactions as referred to in Article 28 paragraph (1) shall be punished with imprisonment a maximum of 6 (six) years and/or a maximum fine of Rp1,000,000,000.00 (one billion rupiah); 2 Factors Causing Online Gambling are: a. Economic factors, b. Social Factors, c. Cultural Factors.